Conflit autour du marché des montagnards Khmirs dans les années 1870 : communauté, immunités et revendications d’autonomie - Fatma Ben Slimane (L’Année du Maghreb)
This research deals with the conflict between the government of the beys of Tunis and the Khmir mountain tribe in the 1870s, concerning their weekly market, Sūq al-Ahad, which was threatened both by new tax burdens and by the French colonial expansion in eastern Algeria. The archives of this conflict make it possible to favor a local approach, centered on the claims of the resource constituted by the market-place and thus to better explore the mobilizations of the actors and the arguments they put forward to defend what they saw as their rights, as well as the way they negotiated them in an increasingly restrictive context.